Familial breast and ovarian cancer : genetics, screening, and management - Morrison, Patrick J. (Patrick John), 1963-; Hodgson, S. V.; Haites, Neva E. (Neva Elizabeth), 1947- (Cambridge University Press, 2002)
Surveys the diagnosis, genetics, screening, prevention and management of familial breast cancer.